Wastewater Generation in Rural Areas of District Budgam, India (International Journal of Innovative Research in Engineering & Management, 2022)
The aim of this study was to study the  waste-water generation through various sources and to  suggest the necessary remedial measures so that it  generation can be lowered as well as the generated waste water can be re-used .Industrial and municipal sources  both contribute to wastewater creation. Initially, as  growth and industrialization progressed, industrial  wastewater generated a substantial amount of wastewater,  whereas municipal wastewater generated a smaller  amount. Wastewater generated by the industrial sector  has been captured, treated, and recycled throughout time  as a result of rising environmental activism, making it  sustainable by its use in the majority of sectors. Due to  the exponential growth of urbanisation, municipal sewage  has increased throughout time, leaving an inextricable  impact on urban perennial water sources such as surface  riverine and ground water treatment. According to census  data from 2011, Jammu and Kashmir has a population of  1.25 million people, up from 1.01 million in 2001.  After 2012, the population began to fall, and calculations  relating to population growth beginning in 2012 resulted  in an average population growth rate of 2.02% each year.  According to estimates from the Central Pollution Control  Board (CPCB), 85 litres per capita per day (LPCD) of  wastewater delivered to each household is returned in the  form of sewage. It's estimated that with an increase in  population consuming water and decreasing waste water  recycling and reuse in the municipal sector, this might  rise to 121 LPCD by 2030.  Based on the CPCB estimates, approximately 62 percent  of total daily water supply, or 187 MLD of water, is  created as city sewage or urban sewage. According to  CPCB records, Class I cities received a total water supply  of 267.42 MLD in 2010, while Class II cities received a  total water supply of 34.24 MLD. This brings the total  amount of water supplied to its residents to 301 MLD.
Keywords: Population Growth; Waste-Water; Treatment Methods; Ground Water; Valley